Security Perception as a Moderating Variable of the Influence of Customer Trust on Repurchase Intention - Atik Andhayani; Efti Novita Sari; Nurul Qisthi; Nur El Ikhsan; Muhammad Fachmi (Yayasan Inovasi Kemajuan Intelektual, 2025)
This research is a quantitative study with an explanatory approach, which uses previous research as the primary material for creating hypotheses, adding novelty elements that are different from previous studies, and testing the hypotheses that researchers make. The primary material that researchers mean in this study is research. The data used in this study is primary data that researchers obtained from Gacoan noodle customers spread across several corners of Indonesia, with the minimum criteria of having shopped more than three times, with a many of 400 customers. The data used in this study were analysed using the innovative PLS 4.0 analysis tool. The result in this article shows that each hypothesis in this study can be proven. The first hypothesis in this study is that the Customer Trust variable can have a positive relationship direction and a significant influence on Employee Performance. Based on the third table above, the Customer Trust variable can have a positive relationship direction and a considerable impact on Repurchase Intention because the P-values ​​are positive and below the significance level of 0.05, namely 0.011. These results show that the higher the Customer Trust, the more likely it is to lead to purchasing decisions, increase customer loyalty, and increase customer comfort. These indicators will ultimately have a good impact and significantly influence Repurchase Intention. The following hypothesis used in this study is that the Security Perception variable can moderate the influence of the Customer Trust variable on the Repurchase Intention variable. This is because the P-values ​​are positive and below the significance level of 0.05, which is 0.000, more significant than the direct testing of 0.011. Increasing Security Perception can further increase Customer Trust because Customers feel safe and comfortable. Ultimately, these rights can have a more significant effect on Repurchase Intention.